Enhancing fraud detection based on technology to improve auditor’s performance in greater Jakarta area ‎ - Maharani, Shaina Melvina; Gartiwa, Khansa Zeirena; Mulyawan, Archie Nathanael (Edelweiss Applied Science and Technology, 2025)
This research investigates the relationship between digital skills and forensic accounting skills in fraud detection and their impact on audit performance among external auditors in the Greater Jakarta area. Using a quantitative descriptive approach, data were collected from 62 external auditors through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The analysis shows that digital skills do not directly affect fraud detection; however, they impact the improvement of forensic accounting skills, which are essential for detecting fraud. The results also indicate that fraud detection does not significantly influence audit performance, suggesting that other factors may mediate this relationship. Nonetheless, digital skills positively influence audit outcomes, demonstrating their critical role in modern auditing practices. This study emphasizes that audit practices should incorporate digital and forensic skills to enhance both fraud detection capabilities and overall audit quality.